Non-biological methods for phosphorus and nitrogen removal from wastewater: A gap analysis of reinvented-toilet technologies with respect to ISO 30500 [version 1; peer review: 2 approved, 1 not approved] - Lena Trotochaud; Brian T. Hawkins; Brian R. Stoner (Gates Open Research, 2019)
The aims of the Reinvent the Toilet Challenge (RTTC) include creation of an off-the-grid sanitation system with operating costs of less than US$0.05 per user per day. Because of the small scale at which many reinvented toilets (RT) are intended to operate, non-biological treatment has been generally favored. The RTTC has already instigated notable technological advances in non-sewered sanitation systems (NSSS). However, increasingly stringent effluent standards for N and P could limit the deployment of current RT in real-world scenarios, despite the urgent need for these systems. The newly adopted ISO 30500 standards for water reuse in NSSS dictate minimal use of chemical/biological additives, while at the same time requiring a 70% and 80% reduction in total nitrogen and phosphorus, respectively. This document provides a brief overview of the mature and emerging technologies for N and P removal from wastewater. At present, the dearth of nutrient removal methods proven to be effective at small scales is a significant barrier to meeting ISO 30500 standards. Closing the gap between RTs and ISO 30500 will require significant investments in basic R&D of emerging technologies for non-biological N and P remediation and/or increased reliance on biological processes. Adaptation of existing nutrient-removal technologies to small-scale NSSS is a viable option that merits additional investigation.